DEVELOPMENT AND EVALUATION OF REMOTE OFFLINE LEARNING MANAGEMENT SYSTEM WITH NETWORK FILE SYSTEM USING INTRANET NETWORKS - Junil P. Rarugal; Nieva Louwah D. Sermona (Universitas Bina Mandiri Gorontalo, 2025)
Abstract— The lack of internet access in underdeveloped nations, particularly the Philippines, exacerbates the digital divide and restricts universal access to ICT. This research developed an alternative standalone offline open educational resources access methods for distant learning and teaching-based eLearning called Remote Offline Learning Management System with Network Files system (ROLMS-NFS) utilizing intranet networks and a Network File System, particularly for far-flung and hinterland schools. The proposed system combines a standard computer unit, a robust Moodle learning management system, and a Network File System database setup. The technology uses an intranet network architecture by connecting two wireless antennas in different locations to create a wireless link. Once linked to the network, teachers, and students can access the e-learning system through local e-learning Uniform Resource Locators (URLs) without total reliance on internet connection and mobile data. As a result, the system makes sharing educational resources easier. It lets students access their lessons, modules, and assignments, take exams and quizzes and even watch video lessons on their laptops, smartphones, and tablets. Further a Technology Acceptance model survey questionnaire was used to assess teacher and student acceptance and intention to use the proposed system by finding its Perceived ease of use, Perceived usefulness, attitude towards use, and behavioral intention to use.